CORRUPTION AND VIOLENCE IN THE NOVELS OF ARAVIND ADIGA (International Journal of Food and Nutritional Sciences, 2023)
Abstract: - Like blood in the body, corruption permeates the entire country. The amount and intensity of Indian culture vary. Its primary cause may be the egotism of the powerful as a result of crime and corruption. This element of criminality, corruption, and violence is depicted throughout Aravind Adiga's novels. According to Adiga's most recent findings, crime and corruption do pay. The Indian economic system, which causes socioeconomic divides and significant social separation, is shown in Aravind Adiga's writings. It restricts social mobility, opportunity, health, and other privileges and pleasures that everyone should have. This novel refers to the significant disparity in the amount of money that is distributed throughout society today. When discussing the circumstances or traits of the Indian servant class, the narrator often brings up the rooster coop. He also uses it to excuse the murder of his master. Crime, corruption, and violence are among the topics covered in Adiga's books. A social structure that separates Indians into upper and lower social strata is the caste system. The caste system is still in place in rural India even though it is allegedly vanishing in urban areas.